2011
DOI: 10.1021/ie2016366
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and UV Absorption Properties of Aurintricarboxylic Acid Intercalated Zn–Al Layered Double Hydroxides

Abstract: Aurintricarboxylic acid (ATA), a UV absorbent, has successfully been intercalated into the interlayer spacing of ZnÀAlÀNO 3 -LDHs precursor through an anion-exchange reaction. The structure and the thermal-and photostability of the intercalated product were investigated by various techniques such as powder X-ray diffraction (XRD), infrared spectroscopy (FT-IR), thermogravimetry and differential thermal analysis (TGÀDTA), and UVÀvis spectroscopy. The increase of the basal spacing from 0.90 to 1.52 nm as observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…For example, after adding 4 wt% of AMO‐Zn 2 Al‐DASDSA LDH, the T 0.05 , T 0.1 , and T 0.5 were significantly increased by 14°C, 24°C, and 43°C respectively. Similar results were also observed in other types of polymer nanocomposites . But when the interlayer anion of LDH is NO3, the T 0.1 and T 0.5 of 4 wt% PP/AMO‐Zn 2 Al‐NO 3 LDH nanocomposites were only increased by 6°C and 23°C, and the T 0.05 was even decreased by 7°C, which is significantly lower than that of PP/AMO‐Zn 2 Al‐DASDSA LDH nanocomposites.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…For example, after adding 4 wt% of AMO‐Zn 2 Al‐DASDSA LDH, the T 0.05 , T 0.1 , and T 0.5 were significantly increased by 14°C, 24°C, and 43°C respectively. Similar results were also observed in other types of polymer nanocomposites . But when the interlayer anion of LDH is NO3, the T 0.1 and T 0.5 of 4 wt% PP/AMO‐Zn 2 Al‐NO 3 LDH nanocomposites were only increased by 6°C and 23°C, and the T 0.05 was even decreased by 7°C, which is significantly lower than that of PP/AMO‐Zn 2 Al‐DASDSA LDH nanocomposites.…”
Section: Resultssupporting
confidence: 84%
“…But when the interlayer anion of LDH is NO3, the T 0.1 and T 0.5 of 4 wt% PP/AMO‐Zn 2 Al‐NO 3 LDH nanocomposites were only increased by 6°C and 23°C, and the T 0.05 was even decreased by 7°C, which is significantly lower than that of PP/AMO‐Zn 2 Al‐DASDSA LDH nanocomposites. Wilkie et al have also demonstrated that LDHs intercalated with organic anions gave significantly increased the resistance to thermal degradation compared to inorganic anion intercalated LDHs. After incorporating 20 wt% MgAl‐C16 LDH, the T 0.1 and T 0.5 increased by 19°C and 48°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally [38], LDHs have the characteristics of anion exchange, which make them adsorb mainly inorganic pollutants such as phosphate [39], borate [40], fluoride [41], and other organic anions [42,43] as well as metal ions in the form of anionic Cr (VI) [44]. The LDH-based composites materials which were prepared by intercalating certain chemical compounds such as crown ether [45], EDTA [46], nitrilotriacetate [47], chromotropic acid [48], aurintricarboxylic acid [49], and polysulfides [50] can adsorb metal ions. However, from the industry side, the dream of these LDH-based adsorbents really used in industry for adsorbing metal ions, is quite hard to realize, because the used guest anions are very expensive.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of PP are usually affected by the UV photo-oxidative degradation under sunlight [43,44]. To improve the anti-UV ability of PP, photostabilizers with 4-Hydroxy-3-methoxybenzoic acid [33] 4-Hydroxy-3-methoxycinnamic acid [33] 4,4 0 -Diaminostilbene-2,2 0 -disulfonic acid [33] p-Aminobenzoic acid [33] Urocanic acid [33] Cinnamic acid [47] p-Methoxycinnamic acid [47] 2-Phenylbenzimidazole-5-sulfonic acid [35,48] 3,6-Dihydroxynaphthalene-2,7-disulfonate [36] 2-Naphthylamine-1,5-disulfonic acid [36,49] 2,3-Dihydroxynaphthalene-6-sulfonic acid [36,50] Aurintricarboxylic acid [51] UV-shielding properties have been added to the PP composite [35,42,[49][50][51]. Figure 11 shows the compared IR reflectance spectra of PP films with and without the addition of ZnAl-BZO-LDHs during photodegradation process [35].…”
Section: Polypropylenementioning
confidence: 99%